1993
DOI: 10.1091/mbc.4.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of epithelial cell-cell adhesion by exogenous expression of a mutated nonfunctional N-cadherin.

Abstract: Cadherins, a family of transmembrane cell-cell adhesion receptors, require interactions with the cytoskeleton for normal function. To assess the mechanisms of these interactions, we studied the effect of exogenous expression of a mutant N-cadherin, cN390A, on epithelial cell-cell adhesion. The intracellular domain of cN390A was intact but its extracellular domain was largely deleted so that this molecule was not functional for cell adhesion. cDNA of cN390A was attached to the metallothionein promoter, and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
145
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(165 citation statements)
references
References 37 publications
18
145
1
1
Order By: Relevance
“…Furthermore, a number of previous observations [14] indicate that other portions of the cadherin molecule are necessary for cell adhesive function. For example, tight cell-cell junctions mediated by cadherin interactions may require anchoring to a complex of cytoskeletal proteins through the cytoplasmic domain and also possibly molecular clustering via lateral interactions in the plasma membrane [33,34]. The present study supports this view in that a single CAD repeat itself does not form a stable dimer or an oligomer.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, a number of previous observations [14] indicate that other portions of the cadherin molecule are necessary for cell adhesive function. For example, tight cell-cell junctions mediated by cadherin interactions may require anchoring to a complex of cytoskeletal proteins through the cytoplasmic domain and also possibly molecular clustering via lateral interactions in the plasma membrane [33,34]. The present study supports this view in that a single CAD repeat itself does not form a stable dimer or an oligomer.…”
Section: Discussionsupporting
confidence: 74%
“…p120 catenin and b-catenin are the prototypic members of a small family of armadillo repeat domain proteins (Daniel and Reynolds, 1995;Hatzfeld and Nachtsheim, 1996;Hatzfeld et al, 2003;Gu et al, 2009;Zhao et al, 2011). All p120 catenins and ARVCF bind the intracellular juxtamembrane region of the cytoplasmic tail of cadherins to maintain strong cell-cell adhesion (Fujimori and Takeichi, 1993;Reynolds et al, 1996;Ireton et al, 2002;Davis et al, 2003;Kausalya et al, 2004;Xiao et al, 2007;Ishiyama et al, 2010). There are four members of the p120 catenin gene family in zebrafish: ARVCF, p120 catenin d1, p120 catenin d2a (also known as NPRAP/Neurojungin), and p120 catenin d2b (also known as Delta-catenin, plakophilin 4 (PKP4), and p0071 catenin).…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of p120-deficient SW48 carcinoma cells showed that restoring p120 expression efficiently rescued proper epithelial morphology by stabilizing E-cadherin and increasing its abundance (Ireton et al, 2002). Previous reports showed that the expression of extracellular domain deleted dominant-negative (DN) cadherins typically downregulated endogenous cadherins (Fujimori and Takeichi, 1993;Kintner, 1992;Nieman et al, 1999;Troxell et al, 1999;Zhu and Watt, 1996). Overexpression of mutated DN-VE-cadherin constructs lacking either the p120 or β-catenin binding sites showed that downregulation of endogenous VE-cadherin was caused by sequestration of p120, but not β-catenin, indicating that p120 plays an essential role in the regulation of cadherin stability (Xiao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%